Dynamical Analysis and Multisim Simulation of a New 4D Generalized Hamiltonian System - Abdul-Kareem, Karam N.; Al-Azzawi, Saad Fawzi (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper constructed a new 4D hyperchaotic system based on the generalized Hamiltonian forms. Through analysis of fundamental dynamical properties, including equilibrium points, stability, dissipative and conservative behaviors, bifurcation diagram, and Lyapunov exponents both numerically and analytically, this system exhibits a rich of dynamic features, encompassing hyperchaotic, chaotic, chaotic 2-tours, and periodic behaviors under certain parameters. Furthermore, the system is translated into an analog electronic circuit and simulated using an oscilloscope device, which achieved consistency between the MATLAB 2021 and Multisim 14.2 software simulations.